Perioperative predictive factors of intracranial meningioma recurrence following surgical resection. (3rd June 2015) - Klironomos, G; Mansouri, A; Kilian, A; Gonen, L; Khan, O; Zadeh, G
Abstract : Background: Meningiomas represent the commonest benign intracranial tumor and surgical resection is the first line treatment. Tumor recurrence after surgical resection is common. The aim of this study is to identify peri-operative predictors of meningioma recurrence following surgical resection Methods: This was a retrospective hospital-based study of all surgical cases between January 1990 and June 2014. Information regarding age, gender, peri-operative imaging parameters such as peri-tumoral edema or post-operative hemorrhage or residual, and grade were collected. Linear and volumetric measurements (of both tumor volume and volume of edema) were collected as well. Results: Overall, 464 patients were reviewed; n=154(34%) percent of patients were male. The grade distribution was: 296 (74.6%) were Grade I, 78 (19.6%) Grade II, and 23 (5.8%) Grade III. Post-operative tumor bed hemorrhage, noted in 119 (29.9%) of cases, and preoperative peri-tumoral edema volume were significant predictors of tumor recurrence following resection (P= 0.002 and 0.037, respectively). These parameters did not correlate with the MIB-1 index, tumour residual, grade of the tumour, or primary versus recurrent presentation. Conclusions: Pre-operative peri-tumoral edema and post-operative tumor bed hemorrhage are independent predictive of tumor recurrence. Identification of other molecular and/or radiological predictive of recurrence factors could add in our understanding of meningioma behavior.